Human rights from the nuremberg doctors trial to the geneva declaration. Persons and institutions in medical ethics and history - Frewer, Andreas (Medicine Health Care and Philosophy, 2010)
The "Universal Declaration of Human Rights" and the "Geneva Declaration" by the World Medical Association, both in 1948, were preceded by the foundation of the United Nations in New York (1945), the World Medical Association in London (1946) and the World Health Organization in Geneva (1948). After the end of World War II the community of nations strove to achieve and sustain their primary goals of peace and security, as well as their basic premise, namely the health of human beings. All these associations were well aware of the crimes by medicine, in particular by the accused Nazi physicians at the Nuremberg Doctors Trial (1946/47, sentence: August 1947). During the first conference of the World Medical Association (September 1947) issues of medical ethics played a major role: and a new document was drafted concerning the values of the medical profession. After the catastrophe of the War and the criminal activities of scientists, the late 1940s saw increased scrutiny paid to fundamental questions of human rights and medical ethics, which are still highly relevant for today's medicine and morality. The article focuses on the development of medical ethics and human rights reflected in the statement of important persons, codes and institutions in the field. © 2010 Springer Science+Business Media B.V.
CRIS-Team Scopus Importer:2025-03-13
Keywords: Declaration of Geneva; History of medicine; Human rights; Medical ethics; Universal Declaration of Human Rights; World Medical Association